2014
DOI: 10.1051/smdo/2013001
|View full text |Cite
|
Sign up to set email alerts
|

Ply stacking sequence optimization of composite driveshaft using particle swarm optimization algorithm

Abstract: -In this paper an attempt has been made to optimize ply stacking sequence of single piece E-Glass/Epoxy, HM Carbon/Epoxy and Boron/Epoxy composite drive shafts using particle swarm optimization (PSOA). PSOA programme is developed using MATLAB V 7 to optimize the ply stacking sequence with an objective of weight minimization. The weight savings of the E-Glass/Epoxy, HM Carbon/Epoxy and Boron/Epoxy shaft are 51%, 87% and 85% of the steel shaft respectively. The optimum results of PSOA obtained are compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Their design variables were damage ratios, the number of damaged elements, and the number of layers. Manjunath and Rangaswamy [54] optimized the stacking sequence of composite drive shafts made of different materials using PSO. The optimum results obtained by PSO are compared with results of GA and found that PSO yields better results than GA. Ghashochi Bargh and Sadr [55] used the PSO algorithm to the lay-up design of symmetrically laminated composite plates for maximization of the fundamental frequency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their design variables were damage ratios, the number of damaged elements, and the number of layers. Manjunath and Rangaswamy [54] optimized the stacking sequence of composite drive shafts made of different materials using PSO. The optimum results obtained by PSO are compared with results of GA and found that PSO yields better results than GA. Ghashochi Bargh and Sadr [55] used the PSO algorithm to the lay-up design of symmetrically laminated composite plates for maximization of the fundamental frequency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A finite element analysis of carbon-epoxy and glass-epoxy drive shaft was carried out to investigate the effect of fibers winding and layer stacking sequence on the critical speed, buckling torque and fatigue resistance and also showed that shear strength is of minor design importance in tube since the failure mode is dominated by buckling [2]. Analysis of buckling hollow laminated composite drive shafts [3,4] describes the theoretical analysis on torsional buckling of composite drive shafts and predicted the torsional buckling load of composite drive shafts with various lay-ups. Study of shear buckling of composite shafts under Torsion Composite Structures [5] gives the effect of boundary conditions and stacking sequence on the strength of the drive shaft.…”
Section: Introductionmentioning
confidence: 99%